Developing a Deep Learning Dance Model for Character Education in Indonesian Junior High Schools - Heni Komalasari; Beben Barnas; Ria Sabaria (Universitas Negeri Semarang, 2026)
This study developed, implemented, and evaluated the Deep Learning Dance Model (DL-DM), a pedagogical model designed to support character development through meaningful dance learning among junior high school students. The model comprises three sequential learning phases: Meaning Exploration, Value Reflection, and Character Expression delivered within a project-based learning framework across four classroom meetings. An adapted research and development (R&D) approach was employed, involving 58 eighth-grade students from two public junior high schools in West Java, Indonesia, over a three-month research period. The model was first trialed at State Junior High School 1 Cicalengka (n = 28), revised based on that trial, and subsequently implemented at State Junior High School 14 Bandung (n = 30). Qualitative and quantitative data were collected through classroom observations, semi-structured interviews, documentation, and a character assessment rubric covering independence, collaboration, communication, and critical thinking. Post-implementation scores were higher than pre-implementation scores across all four dimensions at both schools (Wilcoxon signed-rank test, all p < .001), with medium-to-large effect sizes (r = .49–.61). The rubric showed satisfactory internal consistency (Cronbach’s α = .84) and almost perfect inter-rater agreement across the complete set of double-coded observations (Cohen’s κ = .82). These findings provide preliminary evidence that the DL-DM can serve as an instructional framework for integrating character education into dance learning. Because the study did not include a control group and involved only two schools, further controlled studies in more diverse educational settings are needed before its effectiveness and transferability can be evaluated.